2014
DOI: 10.1210/jc.2014-2702
|View full text |Cite
|
Sign up to set email alerts
|

Routine Screening by Brain Magnetic Resonance Imaging Is Not Indicated in Every Girl With Onset of Puberty Between the Ages of 6 and 8 Years

Abstract: Our data cast doubt on the need of routine screening by brain MRI in girls with idiopathic CPP older than 6 years. Evidence-based criteria to drive clinical decision making about the use of MRI are lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 37 publications
2
76
0
Order By: Relevance
“…In this single-center cohort of patients with SS and PP, a pituitary microadenoma was identified in 18.5% ( n = 346) and 22.8% ( n = 215), respectively. The incidences we report are notably higher than in previous studies of patients with GHD (0.5%) [2] and PP (1.7–5%) [3, 4]. Our study included MRIs performed over a time period where increased scanner resolution and other modern imaging techniques, such as dynamic imaging and increased magnet strength, may have improved detection of microadenomas.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In this single-center cohort of patients with SS and PP, a pituitary microadenoma was identified in 18.5% ( n = 346) and 22.8% ( n = 215), respectively. The incidences we report are notably higher than in previous studies of patients with GHD (0.5%) [2] and PP (1.7–5%) [3, 4]. Our study included MRIs performed over a time period where increased scanner resolution and other modern imaging techniques, such as dynamic imaging and increased magnet strength, may have improved detection of microadenomas.…”
Section: Discussionmentioning
confidence: 87%
“…The rate of intracranial pathologic lesions causing SS/GHD may be larger because our series excluded subjects who had an MRI obtained for other pituitary hormone abnormalities or for nonpituitary reasons that found a mass that was also causing SS. Recent studies have suggested that in PP patients, brain MRIs may have frequent incidental findings without detecting any pathologic findings in 6- to 8-year-old girls [4]. More research is needed to better define patients with SS and PP who are at higher risk of undiagnosed pathologic lesions who would benefit most from MRI to reduce the risk of incidental findings, improve safety, and reduce cost.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI imaging of the head has the highest sensitivity for detecting masses related to the pituitary and hypothalamic regions but it is not warranted for all patients with a suspicion for abnormal puberty. Rather, recent data reports that it is unclear if girls older than 6 years require MRI in the absence of a suspicion for an intracranial mass [11]. As noted earlier, ovaries can be imaged with ultrasound to rule out an adnexal mass, and imaging of the adrenal glands can be accomplished with CT.…”
Section: Physical Signs Of Pubertymentioning
confidence: 99%
“…Precocious puberty secondary to the activation of the hypothalamic-pituitary-gonadal axis is termed central precocious puberty (CPP). CPP may be either idiopathic or associated with central nervous system abnormalities, such as hamartomas and tumors, idiopathic CPP (ICPP) being the most frequent diagnosis in girls [24,25]. The pathophysiology of ICPP is unknown, but girls aged 6-8 years with the onset of puberty may represent the extreme variant of the age range of the onset of normal puberty [26].…”
Section: Introductionmentioning
confidence: 99%